(untitled) - Gimpel, Jean (London, 1977)
The Middle Ages, writes French scholar Jean Gimpel, saw an extraordinary flourishing of technological development throughout Europe. With the era came waterwheels and clock towers, nearly uniform machine parts and improvements in public hygiene, vaulting cathedrals and towering city walls, and a notion of spiritual and earthly progress that promised better things to come. In analyzing the growth of precision in measurement and of the experimental sciences, and in considering the careers of medieval geniuses such as the architect-inventor Villard de Honnecourt, Gimpel clearly conveys the intellectual excitement of the time. Sadly, it was undone by religious intolerance, brutal warfare, and the arrival of the plague as quickly as it rose. --This text refers to an out of print or unavailable edition of this title.
Keywords: Economic history,Technological innovations,Lịch sử kinh tế; Economic aspects,History; Medieval, 500-1500,Thời trung cổ, 500-1500; Europe